Rapid analysis of dried blood spot samples with sub-2-µµm LC––MS/MS. (February 2011) - Mather, Joanne; Rainville, Paul D; Spooner, Neil; Evans, Christopher A; Smith, Norman W; Plumb, Robert S
The use of dried blood and dried plasma spots for storage and transportation of samples derived from clinical trials holds the promise to reduce cost, simplify storage and shipping as well as reducing animal usage. From the bioanalysts'' point of view, these dried-paper samples add an extra layer of complexity to the analysis introducing extra matrix effects from the paper itself and sometimes from antiviral treatments applied to the card. In this article we demonstrate the use of the sub-2-µµm particle LC––MS/MS for the bioanalysis of samples derived from a dried blood spot. The higher resolution provided by these small-particle separations allowed for greater resolution of the analyte from the endogenous components in blood samples and from the card-treatment chemicals. The method -development process was enhanced by the use of MS, which could simultaneously acquire full scan and multiple reaction monitoring data, allowing resolution from metabolites and endogenous matrix components. The use of this approach produced sensitivity levels in the 50––100 pg/ml range and analysis times in the 1––2 min range, which was five-times more sensitive and three-times faster than HPLC. This throughput and sensitivity makes this approach ideal for the analysis of preclinical and clinical studies derived from dried blood spots.